PM.51 Challenges of Managing Pregnancy Complicated by Chronic Kidney Disease Stages 3–5: A Tertiary Centre's Experience. (26th April 2013) - Webster, L; Webster, P; Bibby, A; Lightstone, L
Abstract : Objectives: Establish the obstetric and neonatal outcomes in women with chronic kidney disease (CKD) stages 3–5 attending renal antenatal clinic from 1999 to present. Methods: All women with excretory renal dysfunction (creatinine >110 µmol/L or eGFR < 60 ml/min) prior to their pregnancy were identified from the Obstetric-Renal database. Outcomes assessed were: small for gestational age (SGA) infants (<10th centile) calculated using the GROW1 formula, prematurity (both <37 and <34 weeks), pre-eclampsia and mode of delivery. Results: 67 pregnancies in 55 women complicated by CKD 3–5 were identified. Three twin pregnancies were excluded from the analysis to prevent confounding of multiple gestation. Sufficient data to calculate birth centile was absent for 21 pregnancies. GROW birth centile was therefore calculated in 43 pregnancies, 14 (33%) were below the 10th centile and 25 (58%) were below the 25th centile. Analysis of all 64 pregnancies revealed 19 babies (30%) were delivered before 34 weeks and 36 (56%) were delivered before 37 weeks. All women were delivered before 40 completed weeks. There was one stillbirth at 28 weeks and one neonatal death of a baby born at 31 weeks. 31 (48%) babies required admission to the neonatal unit. Twelve (19%) pregnancies were complicated by pre-eclampsia. In 8 (12%) pregnancies spontaneous labour occurred and in 24 (38%) labour was induced. The other 32 (50%) were planned caesarean sections and the total caesarean section rate was 66%. Conclusions: Pregnancies complicated by CKD stages 3–5 are obstetrically high risk and women should enter pregnancy aware of the possible complications. Reference: Gardosi J, Francis A. Customised Weight Centile Calculator. GROW version 5.16, Year Gestation Network, www.gestation.net